One mechanism of Sishen Pill on diarrhea with kidney Yang deficiency syndrome: influencing metabolic function by intestinal microorganisms and enzyme activity mediates the gut-kidney axis - Zhou, Mengsi; Li, Xiaoya; Xiao, Nenqun; Tan, Zhoujin (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionSishen Pill (SSP), a classic TCM formula, warms the kidney and spleen, astringes the intestine, and stops diarrhea. Emerging evidence suggests that diarrhea with KYDS is linked to gut microbiota imbalance and altered intestinal enzyme activities. At the same time, SSP has been shown to regulate gut microbiota, improve metabolism, and alleviate intestinal disorders. This research investigates how SSP prevents and treats diarrhea by studying the interaction between SSP and intestinal microorganisms.MethodsIn a murine model of diarrhea induced by adenine and Foliuem sennae co-administration, we collected various biospecimens, including intestinal mucosa (ileum and colon), luminal contents, serum, and major organs (kidney, spleen) for comprehensive mechanistic analyses. Techniques such as microbial culture, enzyme activity assays, and HE staining were employed to assess cultivable microbial colony counts, enzyme activity, relevant metabolic indicators, oxidative stress markers, and to observe kidney tissue sections.ResultsThe results indicated that SSP treatment significantly reduced uric acid levels, Escherichia coli (E. coli) count, and amylase activity compared to the spontaneous recovery (MC) group, while the spleen and thymus index, total bacterial count, sucrase activity in contents, protease activity and microbial activity in mucosa were significantly higher than the measurements in MC group. Significant differences were observed in alanine aminotransferase level, Lactobacillus count, Bifidobacterium count, sucrase activity, and microbial activity between the SSP and blank control groups. Serum uric acid levels showed a positive correlation with E. coli colony count and a negative correlation with Lactobacillus colony count. Additionally, total bacterial colony count was negatively correlated with aspartate aminotransferase levels.ConclusionsThe SSP may alleviate diarrhea with kidney Yang deficiency syndrome by reducing E. coli count, enhancing specific enzyme activities, and regulating organ indices and oxidative stress, with the regulatory effects on organ indices and oxidative stress potentially associated with its modulation of E. coli and enzyme activity. This cascade of microbial-enzymatic regulation likely contributes to the normalization of organ indices (e.g., spleen and thymus indices) and alleviation of oxidative stress, as reflected by enhanced superoxide dismutase activity. These findings highlight the multitarget therapeutic potential of SSP in addressing dysfunction in the intestinal-microbiome-enzymatic-organ axis in diarrhea with kidney Yang deficiency syndrome.